Innate immune pathways controlling IL-1beta production and adjuvant-induced T helper 17 cell differentiation - Shenderov, K (2011)
Although adjuvants are critical vaccine components, their modes of action are poorly understood. This has hampered the development of novel adjuvants, and as a result there are very few approved for clinical use. Moreover, none of the clinically-approved adjuvants are able to induce T helper 17 (Th17) CD4+ T cell responses. Th17 cells play important roles in host defense against extracellular bacteria, fungi, and some intracellular pathogens, so understanding how to produce Th17-promoting adjuvants may be valuable for vaccine development. Here, we investigated the mechanisms by which the heat-killed mycobacteria in complete Freund’s adjuvant (CFA) promote T helper 17 (Th17) CD4+ T cell responses. We found that IL-1β / IL-1 receptor signaling on both CD4+ T cells and the non-T cell compartment is required for optimal CFA-induced Th17 differentiation. In addition, we demonstrated that recognition of mycobacterial trehalose dimycolate (cord factor) by mincle / CARD9-dependent signaling and of peptidoglycan by the inflammasome play major roles in adjuvant-induced IL-1β production and Th17 polarization. Importantly, purified cord factor and peptidoglycan administered in mineral oil synergized to recapitulate the Th17-promoting activity of CFA. These data suggest a strategy for the rational design of Th17-skewing adjuvants. In addition to studying IL-1β production in response to microbial stimuli, we have identified a role for endoplasmic reticulum (ER) stress in conditioning cells for IL-1β secretion in response to TLR4 stimulation. Even though the caspase 1 inflammasome is activated in this system, we found that it is dispensable for IL-1β maturation. We show that another IL-1β-cleaving enzyme, caspase 8, is activated in response to ER stress and TLR4 signaling, and may account for the inflammasome-independent processing of IL-1β. Both caspase 8 activation and IL-1β production in this system depend on the signaling adaptor TRIF. As ER stress is known to be induced by obesity and other metabolic stress, as well as during infection, the characterization of this ER stress-induced IL-1β production pathway may help illuminate the link between ER stress and inflammation.